Late Bone Marrow Mononuclear Cell Transplantation in Rats with Sciatic Nerve Crush: Analysis of a Potential Therapeutic Time Window - Usach, Vanina (2024)
After peripheral nerve injury, axon and myelin regeneration are key events for optimal clinical improvements. We have previously shown that early bone marrow mononuclear cell (BMMC) transplantation exerts beneficial effects on myelin regeneration. In the present study, we analyze whether there is a temporal window in which BMMCs migrate more efficiently to damaged nerves while still retaining their positive effects. Adult Wistar rats of both sexes, with sciatic nerve crush, were systemically transplanted with BMMC at different days post injury. Vehicle-treated, naïve, and sham rats were also included. Morphological, functional, and behavioral analyses were performed in nerves from each experimental group at different survival times. BMMC transplantation between 0 and 7 days after injury resulted in the largest number of nested cells within the injured sciatic nerve, which supports the therapeutic value of BMMC administration within the first week after injury. Most importantly, later BMMC administration 7 days after sciatic nerve crush was associated with neuropathic pain reversion, improved morphological appearance of the damaged nerves, and a tendency toward faster recovery in the sciatic functional index and electrophysiological parameters. Our results thus support the notion that even delayed BMMC treatment may represent a promising therapeutic strategy for peripheral nerve injuries.